Development of Islamic Religious Education Learning Media Based on the Maze Chase Wordwall Game on Shalih Children's Materials - Risdayanti; Hasbi, Hasbi; Rahmadani, Ervi (Educational Journal of Learning Technology, 2025)
This research aims to test the reliability of the product and its development process. The research method used is research and development (R&D) with modification of the 4D model, including the definition, design, development, and deployment stages. The subject of the research was a fourth-grade student. Data is collected through surveys, validation sheets, interviews, documentation, and observations. The results of this research are in the form of Islamic Religious Education learning media based on the Maze Chase WordWall game on the material of Children of Shalih. Products are developed through needs analysis, design, expert validation, and trials. The validation results showed that this media was very valid, with a score of 96.42% from material experts, 75% from media experts, and 91.66% from linguists. The practicality test showed a score of 78%, which indicates that this game is feasible and practical to use in learning Islamic Religious Education.